Association between asymptomatic infections and linear growth in 18–24‐month‐old Malawian children. Issue 1 (16th September 2022) - Luoma, Juho; Adubra, Laura; Ashorn, Per; Ashorn, Ulla; Bendabenda, Jaden; Dewey, Kathryn G.; Hallamaa, Lotta; Coghlan, Ryan; Horton, William A.; Hyöty, Heikki; Kortekangas, Emma; Lehto, Kirsi‐Maarit; et al.
Abstract: Inadequate diet and frequent symptomatic infections are considered major causes of growth stunting in low‐income countries, but interventions targeting these risk factors have achieved limited success. Asymptomatic infections can restrict growth, but little is known about their role in global stunting prevalence. We investigated factors related to length‐for‐age Z ‐score (LAZ) at 24 months by constructing an interconnected network of various infections, biomarkers of inflammation (as assessed by alpha‐1‐acid glycoprotein [AGP]), and growth (insulin‐like growth factor 1 [IGF‐1] and collagen X biomarker [CXM]) at 18 months, as well as other children, maternal, and household level factors. Among 604 children, there was a continuous decline in mean LAZ and increased mean length deficit from birth to 24 months. At 18 months of age, the percentage of asymptomatic children who carried each pathogen was: 84.5% enterovirus, 15.5% parechovirus, 7.7% norovirus, 4.6% rhinovirus, 0.6% rotavirus, 69.6% Campylobacter, 53.8% Giardia lamblia, 11.9% malaria parasites, 10.2% Shigella, and 2.7% Cryptosporidium . The mean plasma IGF‐1 concentration was 12.5 ng/ml and 68% of the children had systemic inflammation (plasma AGP concentration >1 g/L). Shigella infection was associated with lower LAZ at 24 months through both direct and indirect pathways, whereas enterovirus, norovirus, Campylobacter, Cryptosporidium, and malaria infections were associated with lower LAZ at 24 months indirectly, predominantly through increased systemic inflammation and reduced plasma IGF‐1 and CXM concentration at 18 months. Abstract : Inadequate diet and frequent symptomatic infections are considered major causes of growth stunting in low‐income countries, but interventions targeting these risk factors have achieved limited success. Asymptomatic infections are common in apparently healthy children in rural Malawi and are associated with reduced linear growth, mainly through systemic inflammation and reduced plasma concentration of insulin‐like growth factor 1 hormone. Key messages: Asymptomatic infections are common in apparently healthy children in rural Malawi. Asymptomatic infections are associated with reduced linear growth, mainly through systemic inflammation and reduced plasma concentration of insulin‐like growth factor 1 hormone. For achieving healthy growth at the population level, adequate nutrition programs may need to be complemented with comprehensive infection prevention and management.